Effects of the Aging Process on Left Ventricular Systolic and Diastolic Synchronicity Indexes: Insights From 160 “Completely” Healthy Volunteers - Kim, Hyung‐Kwan (Clin Cardiol, 2010)
BACKGROUND: Growing attempt to use left ventricular (LV) systolic (LVSIsys) and diastolic (LVSIdia) synchronicity indexes in the process of selecting potential responders to cardiac resynchronization therapy has created a need for normative reference values. HYPOTHESIS: This study sought: (1) to determine normal reference ranges for LVSIsys and LVSIdia, and (2) to assess their relationships to age and conventional parameters reflecting LV systolic and diastolic functions. METHODS: We recruited 160 healthy volunteers (104 men) free of any systemic or cardiovascular disease. Maximal difference and standard deviation of time to peak systolic and peak early diastolic myocardial velocities for LVSIsys and LVSIdia were measured using 6 and 12 segment models. RESULTS: Normal ranges for LVSIsys and LVSIdia obtained in this study were slightly higher than previously reported. The normal aging process did not significantly change LVSIsys, whereas LVSIdia progressively and consistently increased with age. Significant correlations were observed between LVSIdia and parameters representing LV diastolic function, that is, early mitral inflow velocity and its deceleration time, and early mitral annulus velocity. A physiologic increase in LV mass/Ht(2.7) showed a weak, but significant correlation with LVSIdia (r = 0.15–0.22), but not with LVSIsys. On multivariate analysis, an age‐dependent increase in LVSIdia was confirmed. CONCLUSIONS: In this study, we propose age‐specific reference ranges for LVSIsys and LVSIdia. LVSIsys remains stable throughout age groups, whereas LVSIdia progressively increases with age. We believe that the reference values provided here will be useful for defining abnormal LV synchronous contraction and relaxation. Copyright © 2010 Wiley Periodicals, Inc. This work was presented in part at the Annual Scientific Session of the American Society of Echocardiography, Seattle, Washington, June 16–20, 2007.